Stress Measurement During Crack Propagation In Metal Matrix Composites Using Micro-Raman Spectroscopy - Iqbal, AKM Asif; Arai, Yoshio (2016)
The measurement of stress in the SiC particles during crack propagation was investigated by micro raman spectroscopy. The experiment was carried out in situ in the Raman spectroscopy. Experimental results showed that cracks due to monotonic loading propagated by the debonding of the particle/matrix interface and particle fracture. A high decrease in stress was observed with the interfacial debonding at the interface and with the particle fracture on the particle. Moreover, the critical tensile stresses for particle-matrix interface debonding and particle fracture developed in hybrid MMC were also estimated during the crack propagation.